The colours of English alabaster panels Medieval polychromy, production and perception - Schlicht, Markus (PrimaLun@, 2023)
Between c. 1350 and 1550, English sculptors carved thousands of panels depicting religious scenes from alabaster quarries around Nottingham. Exported throughout Europe, these polychrome reliefs were originally usually assembled to form altarpieces. Their coloured epidermis, an integral part of these works that can be termed three-dimensional paintings, has now often disappeared. A multidisciplinary team (art historian, archaeologist, artist and specialist in ancient polychromy, 3D engineers and optodigital researcher) has analysed and reconstructed the polychromy of several of these English panels preserved in the Bordeaux region. The physico-chemical analyses made it possible to determine the nature of the materials used and to recreate the paints used by the alabastermen. These data were used to produce an alabaster facsimile as well as two 3D models with their digital polychromy. As the polychromy of English alabaster works is highly standardised, these examples can be considered as representative of the appearance that the vast majority of the panels must have showed. The study thus allows us to address broader themes, such as the aesthetic and symbolic qualities of the colours used by the alabastermen, or the way in which these were perceived by the medieval viewer.